1988
DOI: 10.1128/jb.170.2.512-521.1988
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of lipopolysaccharides from Pseudomonas aeruginosa: analysis of lipopolysaccharide chain length

Abstract: Lipopolysaccharide (LPS) from smooth strains of Pseudomonas aeruginosa 503, PAZ1, PA01715, PA01716, and Z61 was fractionated by gel filtration chromatography. LPS samples from the first four strains, all PAO1 derivatives, separated into three major size populations, whereas LPS from strain Z61, a Pac K799/WT mutant strain, separated into two size populations. When column fractions were applied to sodium dodecyl sulfate-polyacrylamide gels in their order of elution, molecules of decreasing size were resolved, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
137
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 59 publications
(80 reference statements)
10
137
0
Order By: Relevance
“…LPS is a glycolipid composed of three distinct regions: lipid A, core oligosaccharide, and O antigen. P. aeruginosa produces two forms of O antigen, which are the homopolymeric A band and the heteropolymeric B band (15,21). The gene clusters associated with the biosynthesis of Aband and B-band O antigen in P. aeruginosa have been well characterized (for reviews, see references 18 and 22).…”
mentioning
confidence: 99%
“…LPS is a glycolipid composed of three distinct regions: lipid A, core oligosaccharide, and O antigen. P. aeruginosa produces two forms of O antigen, which are the homopolymeric A band and the heteropolymeric B band (15,21). The gene clusters associated with the biosynthesis of Aband and B-band O antigen in P. aeruginosa have been well characterized (for reviews, see references 18 and 22).…”
mentioning
confidence: 99%
“…Gram-negative bacteria have a negative net surface charge due to the negatively charged functional groups of the lipopolysaccharide (LPS) layer (Costerton et al, 1974). Mg 2 + acts to stabilize bacterial membranes through the bridging of the negative charges of LPS functional groups, including phosphates, phosphatidic acid, and 2-keto-3-deozyoctulosonic acid (Schindler and Osborn, 1979;Rivera et al, 1988;Amro et al, 2000). Mg 2 + will also bind to other membrane constituents, including inorganic phosphates and teichoic acids (Heptinstall et al, 1970;Naumann et al, 1989;van Veen, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The SDS-polyacrylamide gel of the column fractions, when applied in order of elution, revealed two major size populations: the A-band or common antigen LPS and an 0-serotype-like LPS which is composed of core and lipid A with no or one 0-repeat unit (short-chain [SC] or B-band LPS; results not shown). As indicated in earlier studies (22,23), the SC-LPS fraction contains the majority of the molecules. The column elution profile confirmed earlier results which indicated that this strain is defective in the synthesis of 0 antigen (3).…”
mentioning
confidence: 92%
“…The mixture was incubated with mild agitation at 20°C for 2, 3, 4, 5, and 24 h. An aliquot of 50 ,lI of the digested LPS was mixed with an equal volume of electrophoresis sample buffer (containing 4% SDS) and applied to an SDS-polyacrylamide gel. Electrophoresis was performed as previously described (22), and the gels were silver stained. The SDS-polyacrylamide gels of the digested samples showed that the polysaccharide chain of the A-band LPS was completely hydrolyzed by phage A7 within 2 h (Fig.…”
mentioning
confidence: 99%